2018
DOI: 10.1097/prs.0000000000003962
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Incidences following Facial Plastic Surgery Procedures: Incorporating FACE-Q Data to Improve Patient Preparation

Abstract: In the growing facial cosmetic surgery industry, patient perspective is critical as a determinant of success; therefore, incorporation of evidence-based patient-reported outcome data will not only improve patient expectations and overall experience, but will also reveal adverse event incidences that were previously unknown. Given that there is incomplete overlap between patient-reported and physician-reported adverse events, presentation of both data sets in the consultation setting will improve patient prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This was also noted when it was found that procedures at the lower eyelid region did not change satisfaction with facial geometry, perhaps because the physical change was not so pronounced. However, these differences in perceived outcome may differ between patients and surgeons, revealing the complexity of satisfaction after rhytidoplasty and other facial aesthetic procedures (3,7,14).…”
Section: ' Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was also noted when it was found that procedures at the lower eyelid region did not change satisfaction with facial geometry, perhaps because the physical change was not so pronounced. However, these differences in perceived outcome may differ between patients and surgeons, revealing the complexity of satisfaction after rhytidoplasty and other facial aesthetic procedures (3,7,14).…”
Section: ' Discussionmentioning
confidence: 99%
“…Interest in facial rejuvenation has been growing, resulting in an increase in demand for plastic surgery, especially rhytidoplasty (1)(2)(3)(4)(5)(6)(7). In the USA, there was a 21.9% increase in the number of rhytidoplasty procedures from 2016 to 2017 (8).…”
Section: ' Introductionmentioning
confidence: 99%
See 3 more Smart Citations